Analisis Nilai Pendidikan Karakter dalam novel 172 Days karya Nadzira Shafa Melalui Pendekatan Hermeneutika Paul Ricouer: Analysis of Character Education Values in the Novel '172 Days' by Nadzira Shafa through Paul Ricoeur’s Hermeneutic Approach - Dini Andiyani; Nuzul Tenriana; Rusman Latif; Imran Imran; Mansur Ga'ga (Universitas Tidar, 2025)
This study aims to find the character education values in Nadzira Shafa's novel